2019
DOI: 10.21203/rs.2.9190/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting Self-management in Iranian Tuberculosis Patients: A Path Analysis Model

Abstract: Background Tuberculosis is a chronic infectious disease that, if not treated and managed properly, increases the Multi Drug Resistance (MDR). Self-management behaviors can reduce the progression of illness. Although various factors affect self-management, no study has not been conducted on the self-management tuberculosis through path analysis. This study evaluated the factors affecting self-management in tuberculosis patients using path analysis. Methods This study was a cross-sectional study and was done … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…However, when evaluated separately, treatment default was higher in people under 43 years old (27) , while death was higher in people aged ≥30 years old (27) . Thus, it seems that TB treatment default in the prison unit is more common among young people, consistent with a study showing that older individuals with the disease were more concerned with self-care and cared more for their health (29) . Despite this, everything indicates that older people are more likely to die, and this is due to the overlapping of comorbidities in this population and greater toxicity of antituberculous drugs in these individuals (30) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, when evaluated separately, treatment default was higher in people under 43 years old (27) , while death was higher in people aged ≥30 years old (27) . Thus, it seems that TB treatment default in the prison unit is more common among young people, consistent with a study showing that older individuals with the disease were more concerned with self-care and cared more for their health (29) . Despite this, everything indicates that older people are more likely to die, and this is due to the overlapping of comorbidities in this population and greater toxicity of antituberculous drugs in these individuals (30) .…”
Section: Discussionsupporting
confidence: 82%
“…Regarding education, a survey showed that individuals with more than eight years of education were less likely to discontinue treatment and die from other causes (27) . Another study shows that the lower level of knowledge about TB was associated with people with low level of education (33) , who are less concerned with self-care (29) and, therefore, discontinue treatment and are subject to a higher risk of death. Thus, it is worth emphasizing the importance of health education actions aimed at these individuals, with a view to increasing the level of knowledge about the disease and its treatment, as well as the need to maintain such treatment even after symptoms improve (34) .…”
Section: Medicalmentioning
confidence: 99%